High-efficient and defect tolerant Co2MnSb ternary Heusler alloy for spintronic application - Enamullah; Lee, Seung-Cheol (Elsevier BV, 2018)
In this article, we propose an antisite defect tolerant ternary Heusler alloy, Co2MnSb, which is highly efficient for spintronic applications. Using ab-initio Density Functional Theory (DFT), we study the effect of experimentally observed intrinsic point defect (antisite defect) and lattice constant (L-c) on the halfmetallic characteristics, mechanical stability and magnetic properties of Co2MnSb. Ab-initio simulation predicts halfmetallic ferromagnetic characteristics with a high value of total magnetic moment, 6.00 (5.92) mu(B)/f .u. and large Curie temperature (T-C), 1109 K (1094 K) at relaxed (experimental) L-c. Halfmetallic characteristics and mechanical stability are sensitive to L-c variation. Experimentally, it has been observed that intrinsic defects in Heusler alloys always degrades the halfmetallic characteristics and spin polarization. Hence, all the possible binary and ternary kind of antisite defects between the transition metals and the non-magnetic p-block element of Co2MnSb have been simulated upto the disorder concentration ('x') of 11.1%. Our theoretical analysis reveals that even in presence of antisite disorder, the alloy preserves its halfmetallic characteristics specially at lower disorder concentrations. However, electronic density of states and total magnetic moment are affected significantly in presence of disorder. In some disordered alloys, total magnetic moment exceeds beyond 6.00 mu(B), indicating towards the higher value of T-C with respect to the parent compound. Formation energy of particular disordered alloys compete with the formation energy of parent alloy, makes the compound defect tolerant material. Halfmetallic characteristics, high magnetic moment and large T-C make the defect tolerant Co2MnSb alloy highly efficient for spintronic applications. (C) 2018 Elsevier B.V. All rights reserved.